Covid-19 has brought back the necessity of the welfare state: The Greek case - Tzagkarakis, Stylianos-Ioannis; Pappas, Ilias; Kritas, Dimitrios (HAPSc Policy Briefs Series, 2020)
In Europe, despite systemic, functional and structural differences, the welfare state has been a key component of the state after World War II. In recent decades, the former has been accused for inflating government spending and turning people into passive recipients of benefits and services. For this reason, and for several more, such as globalization, the transforming nature of employment and the changing family patterns, the welfare state has undergone the necessary reforms in order to combine the effectiveness and efficiency of its services and benefits. The outbreak of 2009 economic crisis has created tremendous problems to the welfare state, especially in the hardest hit countries, such as Greece. Although these structural problems and inefficiencies existed, the Greek state in general and the National Health System (NHS) in particular have handled the coronavirus successfully, making the country an example for the others but also stressing the necessity to consolidate the welfare state and specifically the NHS. This paper aims to analyze the way the Greek state handled the coronavirus crisis while underlie the importance of the welfare state especially in times of crisis and the challenges that coronavirus has created.